2015
DOI: 10.4236/ajps.2015.63051
|View full text |Cite
|
Sign up to set email alerts
|

Flowering of Sugarcane Genotypes under Different Artificial Photoperiod Conditions

Abstract: Flowering is essential in any breeding programme, particularly in genetic introgression programmes in which flowering synchronism is required. In this work, 16 sugarcane genotypes were evaluated using three different flowering-inductive photoperiod treatments (30 s, 45 s, and 1 min of a daily photoperiod decrease from 12 h 55 of light). Each genotype was planted in 43 L pots (equal proportion of soil, sand, and substrate) with three tillers per pot. Plants with 4 to 6 internodes were placed in a photoperiod fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Within certain study sites (e.g., site 5), some cultivars showed pollen viability of 70%, while others had <10%. A similar study in Brazil reported 100% viable pollen in some cultivars while others showed pollen viability of <9%, under the same environmental conditions (Melloni et al, 2015 ). Pollen viability has also been closely associated with genotype (Nair, 1975 ; Pagliarini, 2000 ; Melloni et al, 2015 ).…”
Section: Discussionmentioning
confidence: 86%
“…Within certain study sites (e.g., site 5), some cultivars showed pollen viability of 70%, while others had <10%. A similar study in Brazil reported 100% viable pollen in some cultivars while others showed pollen viability of <9%, under the same environmental conditions (Melloni et al, 2015 ). Pollen viability has also been closely associated with genotype (Nair, 1975 ; Pagliarini, 2000 ; Melloni et al, 2015 ).…”
Section: Discussionmentioning
confidence: 86%
“…Early and late flowering in different varieties might be due to the difference in maturity period of the varieties/genotypes. On the other hand Melloni et al (2015) illustrated that one of the difficulties found in their work was the balance between induction and flowering of the genotypes within and among the treatments. In the present study, some genotypes that did not synchronized with each other at the full flowering stage when planted in the same season, we found them synchronized when they planted in different seasons, such as plant cane in autumn season (Table 2), where the full flowering of genotype G2006-3 was after 502.67 days and genotype BO41-227 was after 455.67 days.…”
Section: Results Presented Inmentioning
confidence: 99%
“…In this crop, flowering shows a range of variation among the varieties. Melloni et al (2015) reported that flowering is essential to any breeding programme to promote crosses. Floral induction is usually observed prior to panicle emergence through stalk elongation, lateral sprouting and flag leaf emission.…”
Section: Results Presented Inmentioning
confidence: 99%
“…Further improvements in the number of genotypes that can be flowered in our greenhouse might be obtained by adjusting the rate of decline in photoperiod. Recently, two studies found that a photoperiod decline of 40-45 sec d -1 was likely superior to 30 or 60 d -1 for flowering most sugarcane genotypes (Berding et al, 2010;Melloni et al, 2015).…”
Section: Flowering Sugarcane At 40 Nmentioning
confidence: 99%